Effects of particle length and maturity stage of whole crop barley silage on feed intake, chewing activity and eating behaviour by growing dairy steers - Sahlin, Ann (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Whole crop cereal silage has proven to be a good and flexible feed alternative to growing cattle and can be fed alone or together with other forage sources. Whole crop silages constitute a less homogenous material compared to grass silage, with awns rich in starch and stalks with a high fiber concentration. A regular intake of fibrous materials, such as whole crop silage, is of importance to stimulate chewing and to ensure proper digestion and a healthy rumen environment of cattle and other ruminant animals.